2005
DOI: 10.1007/s10895-005-0213-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lanthanide Luminescence Using Silver Nanostructures: Opportunities for a New Class of Probes with Exceptional Spectral Characteristics

Abstract: The photophysical effects of europium tetracycline immobilized in thin polyvinyl alcohol films coated onto silver nanostructures have been investigated. Complimentary to recent reports from our laboratories that the close proximity of luorophores to silver nanostructures can enhance their intrinsic radiative decay rate, we show that up to a 16-fold enhancement in lanthanide luminescence is possible, accompanied by a notable reduction in luminescence lifetime. These results suggest the potential future developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 26 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…The competition between quenching and enhancing effects is well exemplified in the body of work on the effect of silver nanoparticles and silver island films (SIF) on the luminescence properties of Eu 3 + -based phosphors [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The consensus appears to be that a net (and typically modest) enhancement of Eu 3 + ( 5 D 0 ) emission can be achieved using SIFs and colloidal films of interacting Ag nanostructures, whereas the effect of isolated Ag nanoparticles is less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…The competition between quenching and enhancing effects is well exemplified in the body of work on the effect of silver nanoparticles and silver island films (SIF) on the luminescence properties of Eu 3 + -based phosphors [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The consensus appears to be that a net (and typically modest) enhancement of Eu 3 + ( 5 D 0 ) emission can be achieved using SIFs and colloidal films of interacting Ag nanostructures, whereas the effect of isolated Ag nanoparticles is less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Since the fluorescence emission from SIFs is significantly larger than those from blank glass slides, the contribution of fluorophore / protein coverage to the increased fluorescence emission has to be determined for accurate evaluation of metal nanoparticle-deposited surfaces for MEF applications. Despite the presence of numerous publications on MEF phenomenon [16-18] and MEF-based applications [15, 19, 20], the quantitative comparison of fluorophore or protein surface coverage on SIFs and blank glass slides was never investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous novel lanthanide complexes have been synthesized by different methods [14][15][16]. It has been shown that the luminescence of lanthanide complexes can be enhanced by silver island films deposited on quartz or glass slides [17].…”
Section: Metal-enhanced Fluorescence Surface Plasmon Resonance Silvmentioning
confidence: 99%
“…Numerous novel lanthanide complexes have been synthesized by different methods [14][15][16]. It has been shown that the luminescence of lanthanide complexes can be enhanced by silver island films deposited on quartz or glass slides [17].In this paper, a detailed investigation of MEF from lanthanide chelates near continuous Ag thin films and noncontinuous Ag island surfaces is reported. The fluorescence emission of the lanthanide chelates was approximately 2.5 times more intense on a continuous silver thin film than on a quartz substrate.…”
mentioning
confidence: 99%